Penggunaan Handphone dan Dampaknya bagi Aktivitas Belajar - Erni Nuraliyah; Ahmad Fadilah; Elis Handayaningsih; Ernawati Ernawati; Santi Librayanti Oktadriani (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The rapid advancement of information and communication technology affects every aspect of human life. The field of education is no exception. For communication purposes, cellphones can have positive and negative effects on student learning activities. The purpose of this study was to determine the effect of using mobile phones on the learning activities of junior high school students in Jakarta. This study uses a qualitative method. An interview study was used to explore the impact of cell phone use on ten students. This study produces data that the use of mobile phones affects student learning activities in high school. From 10 respondents, it can be assumed that the use of mobile phones with an average duration of 2 hours greatly affects student learning activities. But cell phones also have a bad impact. Among them, it interferes with eye health, makes students forget time to study, and sees pictures that are inappropriate for students to see. The fact states that 100 percent of students are dependent on cellphones.